Cadophora species from marine glaciers in the Qinghai-Tibet Plateau: an example of unsuspected hidden biodiversity - Bingqian Zhang; Xiaoguang Li; Guojie Li; Qi-Ming Wang; Manman Wang (IMA Fungus)
Abstract Large numbers of marine glaciers in the Qinghai-Tibet Plateau are especially sensitive to changes of climate and surface conditions. They have suffered fast accumulation and melting and retreated quickly in recent years. In 2017, we surveyed the cold-adapted fungi in these unique habitats and obtained 1208 fungal strains. Based on preliminary analysis of ITS sequences, 41 isolates belonging to the genus Cadophora were detected. As one of the most frequently encountered genera, the Cadophora isolates were studied in detail. Two phylogenetic trees were constructed: one was based on the partial large subunit nrDNA (LSU) to infer taxonomic placement of our isolates and the other was based on multi-locus sequences of LSU, ITS, TUB and TEF-1α to investigate more exact phylogenetic relationships between Cadophora and allied genera. Combined with morphological characteristics, nine Cadophora species were determined, including seven new to science. Among the new species, only C. inflata produces holoblastic conidia and all the others express phialidic conidiogenesis. All isolates have optimum growth temperature at 20 °C or 25 °C. With more species involved, the currently circumscribed genus became obviously paraphyletic. All members are clustered into two main clades: one clade mainly includes most of the Cadophora species which have phialidic conidiogenesis and we refer to as ‘Cadophora s. str.’; the remaining Cadophora species have multiform conidiogenesis and are clustered in the second clade, with members of other genera in Ploettnerulaceae interspersed among the subclades. The results show a high diversity of Cadophora from marine glaciers in the Qinghai-Tibet Plateau and most of them are novel species.